The Joint Effect of a Combination of Components From the Fruit of Crataegus pinnatifida Bge. Var. major N.E. Br. and the Root of Salvia miltiorrhiza Bge. With Exercises on Swimming in Focal Cerebral Infraction in Rat - Ding, Shilan; Wang, Wei; Yin, Xiaojie; Wang, Lan; Gong, Leilei; Liao, Fulong; Liang, Rixin (Frontiers in Physiology, 2020)
Background: In our previous study, we found that the combination of a traditional Chinese medicine (TCM) and swimming could prevent atherosclerosis through a synergistic interaction. However, whether the combined application of active components from the fruit of Crataegus pinnatifida Bge. Var. major N.E. Br. (CP) and the root of Salvia miltiorrhiza Bge. (SM) and swimming has been effective in the prevention and treatment of focal cerebral infraction remained unclear. The present work aimed to investigate the joint effects of CPSM extract with swimming on focal cerebral infraction in rats and its underlying mechanisms. Method: A photochemical method of the combination of Rose Bengal (RB) injection and cold-light source irradiation was performed to establish the rat focal cerebral thrombosis model. The pathological changes of the brain were observed by a DCP-7030 laser multifunction machine, and the protein levels of von Willebrand factor (vWF), vascular cell adhesion molecule-1 (VCAM-1), and intercellular adhesion molecule-1 (ICAM-1) were detected by Western blotting. Blood samples were collected to assay tissue plasminogen activator (t-PA), plasminogen activator inhibitor type-1 (PAI-1) , endothelin-1(ET-1), 6-keto-prostaglandin F1a (6-keto-PGF1α) , and thromboxane B2 (TXB2). Finally, the gene expression of t-PA, PAI-1 and ICAM-1 in human umbilical vein endothelial cells (HUVECs) stimulated by TNF-α was assayed via real-time (RT) quantitative polymerase chain reaction (qPCR). Results: The joint effects of CPSM extract and swimming indicated significant interactions, including increased blood perfusion; increased serum t-PA and 6-keto-PGF1α; decreased serum PAI-1 and TXB2; decreased protein levels of vWF, VCAM-1 and ICAM-1; and decreased ICAM-1 gene expression. Conclusion: This research demonstrated that the combined therapy of CP and SM extracts with swimming could prevent focal cerebral infraction through interactions on the regulation of vascular endothelial functions and inflammatory factors. It stresses the promising effects of the drugs and shear stress of blood flow in prevention and treatment of thrombosis. The mechanism may be related to regulating the protein expression of vWF, VCAM-1 and ICAM-1, and down-regulating the gene expression of ICAM-1.